2022
DOI: 10.3390/plants11141785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Composition, Physicochemical Parameters, and Antioxidant and Antibacterial Activity of the Essential Oil of Cultivated and Wild Mexican Oregano Poliomintha longiflora Gray

Abstract: Mexican oregano Poliomintha longiflora Gray located in the municipality of Higueras, Nuevo Leon, Mexico was collected during the autumn (September, OCO), winter (January, OCI) and summer (June, OCV) seasons, under cultivation conditions. It was also collected in wild conditions during the autumn (OSO). Essential oil (EO) was extracted from leaves and the color, refractive index and density were reported. The EO yield, antioxidant activity by ORAC assay, thymol and carvacrol concentration and antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These results differ from those found in the wild and cultivated oregano analyzed in this study but are similar to those observed in oregano obtained under controlled conditions (greenhouse) ( Table 1 ). Similarly, other reports have indicated that cultivated oregano ( O. dictamnus ) in northern Mexico contains over 47% carvacrol and no thymol [ 33 ], indicating that wild oregano oil has significantly higher carvacrol levels compared with cultivated oregano in terms of thymol [ 16 ]. Sarrazin et al [ 53 ] reported that carvacrol was the main component in the composition of the EO of Lippia origanoides produced during both the rainy and dry seasons, with 43.5% and 41.4%, respectively, followed by thymol, with 10.7% and 10.6%, indicating a low difference between the analyzed seasons.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…These results differ from those found in the wild and cultivated oregano analyzed in this study but are similar to those observed in oregano obtained under controlled conditions (greenhouse) ( Table 1 ). Similarly, other reports have indicated that cultivated oregano ( O. dictamnus ) in northern Mexico contains over 47% carvacrol and no thymol [ 33 ], indicating that wild oregano oil has significantly higher carvacrol levels compared with cultivated oregano in terms of thymol [ 16 ]. Sarrazin et al [ 53 ] reported that carvacrol was the main component in the composition of the EO of Lippia origanoides produced during both the rainy and dry seasons, with 43.5% and 41.4%, respectively, followed by thymol, with 10.7% and 10.6%, indicating a low difference between the analyzed seasons.…”
Section: Discussionmentioning
confidence: 76%
“…The results indicated that all analyzed oregano oils possess a high potential to neutralize free radicals ( Table 2 ). The AoA of essential oils from different species known as oregano has been reported by several authors [ 3 , 16 , 17 , 20 , 22 , 47 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Although the results obtained in this study for the AoA of the EOE are comparable to those described in other regions of the world, they also turn out to be significantly higher than the published results ( Table 3 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Regarding the metal chelating potential of EOs, only the EO from basil was active with 1.34 mg EDTAE/g, but others showed no chelating ability. The spent extracts from the tested Lamiaceae species (especially basil and oregano) contained significant antioxidant properties [55][56][57]. Consequently, the byproducts of post-distillation can be considered rich sources of natural antioxidants with potential pharmaceutical and nutraceutical applications.…”
Section: Antioxidant Activity Of Essential Oils Total Spent and Resid...mentioning
confidence: 99%
“…On the other hand, the density of the essential oils was determined using the mass over volume formula [37,38].…”
Section: Measurement Of Refractive Index and Density Of Essential Oilsmentioning
confidence: 99%